2018
DOI: 10.1055/s-0038-1675371
|View full text |Cite
|
Sign up to set email alerts
|

An Electronic Medical Record in Pediatric Medical Education: Survey of Medical Students' Expectations and Experiences

Abstract: Objective This study sought to quantitatively characterize medical students' expectations and experiences of an electronic health record (EHR) system in a hospital setting, and to examine perceived and actual impacts on learning. Methods Medical students from July to December 2016 at a tertiary pediatric institution completed pre- and postrotation surveys evaluating their expectations and experience of using an EHR during a pediatric medicine rotation. Survey data included past technology experienc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 26 publications
1
7
0
Order By: Relevance
“…Additionally, in Australia, where billing and documentation requirements differ dramatically from the United States, surveyed medical students have readily engaged with the EHR and found it enhanced their learning and the clinical feedback they received. 10,11 These finding are in line with key tenets of experiential learning in adult learning theory. 12 Newer pedagogic models have also suggested enhanced value of authentic activity and assessment in fostering meaningful learning, 13 which may also support enhanced experiential learning when the learner engages in activities that have an audience outside the constructed educational environment (other health care providers and CMS in this case).…”
Section: Discussionsupporting
confidence: 82%
“…Additionally, in Australia, where billing and documentation requirements differ dramatically from the United States, surveyed medical students have readily engaged with the EHR and found it enhanced their learning and the clinical feedback they received. 10,11 These finding are in line with key tenets of experiential learning in adult learning theory. 12 Newer pedagogic models have also suggested enhanced value of authentic activity and assessment in fostering meaningful learning, 13 which may also support enhanced experiential learning when the learner engages in activities that have an audience outside the constructed educational environment (other health care providers and CMS in this case).…”
Section: Discussionsupporting
confidence: 82%
“…The actual usage of EHRs was not measured. However, several studies have used surveys as a tool to understand medical students’ experience with using medical records and their impact on education [ 18 , 20 , 42 ]. Future research may depend on actual user data that can be extracted from EHR systems and reflect actual usage.…”
Section: Discussionmentioning
confidence: 99%
“…In one study, researchers quantitatively characterized medical students' expectations of an EHR system in a hospital setting and impact on learning. Results showed that medical students recognized clinical advantages, did not consider their ability to interact with patients impaired, and thought EHR marginally improved feedback from clinicians [18].…”
Section: Electronic Health Recordsmentioning
confidence: 99%